2021
DOI: 10.1186/s40663-021-00321-z
|View full text |Cite
|
Sign up to set email alerts
|

Different mechanisms underlying divergent responses of autotrophic and heterotrophic respiration to long-term throughfall reduction in a warm-temperate oak forest

Abstract: Background There are many studies on disentangling the responses of autotrophic (AR) and heterotrophic (HR) respiration components of soil respiration (SR) to long-term drought, but few studies have focused on the mechanisms underlying its responses. Methods To explore the impact of prolonged drought on AR and HR, we conducted the 2-year measurements on soil CO2 effluxes in the 7th and 8th year of manipulated throughfall reduction (TFR) in a warm-t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The forest type, a vital part of the stand structure, can affect the variability in the properties of aboveground litter and belowground root biomass and distribution [56,71], which could in turn affect the responses of forest soil respiration to precipitation changes [17,45,[72][73][74]. Soil CO 2 emissions in coniferous forests appear to be insensitive to increased TF (Figure 2b) compared with the control, whereas the responses of the soil CO 2 emissions to TF reduction are more negative in coniferous and mixed forests than in broadleaf forests (Figure 2a).…”
Section: Throughfall Effects On Soil Co 2 Emissions Vary With Forest ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The forest type, a vital part of the stand structure, can affect the variability in the properties of aboveground litter and belowground root biomass and distribution [56,71], which could in turn affect the responses of forest soil respiration to precipitation changes [17,45,[72][73][74]. Soil CO 2 emissions in coniferous forests appear to be insensitive to increased TF (Figure 2b) compared with the control, whereas the responses of the soil CO 2 emissions to TF reduction are more negative in coniferous and mixed forests than in broadleaf forests (Figure 2a).…”
Section: Throughfall Effects On Soil Co 2 Emissions Vary With Forest ...mentioning
confidence: 99%
“…The SEM analysis showed that the effect sizes of fine root biomass, soil microbial biomass and dissolved organic C content (e.g., lnR roots , lnR mbc and lnR DOC ) played a substantial role in regulating annual soil CO 2 emissions under the altered TF conditions (Figure 7). The changes in soil microbial biomass C and fine root biomass upon altered precipitation would affect soil heterotrophic and autotrophic respiration [28,73,74], which is likely related to the changes in the lnR CO2 values among the experimental categories. To date, only 10 paired observation data points are available showing the responses of soil heterotrophic respiration and autotrophic res-piration to decreased precipitation in temperate (n = 7) and subtropical broadleaf forests (n = 3) [21,28,73,74,90,91].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation